Qualitative assessment the effect of glucose on hydrogel used for nanomedicine drug delivery - Md Nasruddin, Melisa Sofea; Mohamed Suffian, Izzat Fahimuddin; Zakaria, Siti Fatimah; Hamzah, Nurasyikin; Che Othman, Siti Fairuz (IIUM Press, 2023)
Oral cancer is the sixth among the most common pathological types of cancer in the world and its prevalence is increasing in many countries. The conventional treatments known for this disease are by combination of surgery, chemotherapy as well as radiotherapy. The emergence of the nanoparticles drug delivery system which applies the use of topical drugs becomes a better option in the oral cancer therapy due to its high efficiency of drug delivery options. Therefore, this study aims to characterize hydrogels to be used for effective localized drug delivery in the oral cancer treatment. The hydrogels studied in this project involve three types of natural polysaccharides which were kappa-carrageenan, iota-carrageenan, and xanthan gum. The carrageenan hydrogels were formulated with two different concentrations where iota-carrageenan (1.0% and 1.5%) and kappa-carrageenan (0.5% and 1.0%). While xanthan gum was formulated with three different concentrations (1.0%,1.5% and 2.0%). All hydrogels were added with different glucose concentrations (5%, 10% and 15%). The effects of sugar on the physical properties of the carrageenan were studied qualitatively. Result concluded ι- carrageenan and xanthan gum would be the suitable candidates to be used in oral nanoparticle drug delivery system.